Does Official Development Assistance Affect Donor's Export? Case of Korea - Bobae Noh; Almas Heshmati (Institute of Labor Economics (IZA), 2017)
This paper aims to estimate the impact of bilateral Official Development Assistance (ODA) provided by Korea on its bilateral export to recipient countries. The empirical analysis is based on data from 1996 to 2014 with 121 recipient countries. Although the two models of determinants of ODA and its export effectiveness are highly interrelated, this kind of simultaneous model specification with two-ways causal relationship has not been conducted in the past. Employing a three-stage least squares estimation method leads to accounting for two-ways causal relationships between ODA and export while the endogeneity and sample selection bias are accounted for. Through using the gravity model in analysis of Korea's aggregated export data, the positive effect of bilateral ODA is confirmed when fixed unobserved effects are controlled. The model is further generalized by disaggregation of ODA into its underlying types. The results show that, humanitarian aid and loan-type aid turn out to be effective types of ODA to influence export positively. In terms of Korea's ODA allocation, the finding suggests that there is a two-stage decision making process in aid provision. In the first stage, a humanitarian purpose of aid dominates responding to lower income and disaster experienced countries' needs, even when lower bilateral trade prevails. The second stage is to make a decision regarding the size of ODA to selected recipient countries, and this presents a mixed purposes of giving ODA aiming at higher importer countries.
Keywords: F14; F21; F35; 330; gravity model; bilateral Official Development Assistance; bilateral export; three-stage least squares; Korea